Der "gesäuberte" Antifaschismus : die SED und die roten Kapos von Buchenwald ; Dokumente - Niethammer, Lutz 1939- Hrsg; Hartewig, Karin 1959-; Stein, Harry 1956-; Wannemacher, Leonie (Akad.-Verl, 1994)
Dokumente; Quellen